PEMANFAATAN WEBSITE DALAM PERCEPATAN PEMBANGUNAN DI KABUPATEN LUWU - Suandi, Nahda Cantika; Mappamiring, Mappamiring; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The main aim of using websites to accelerate village development is to reduce the gap between urban areas. This research uses descriptive qualitative research. The results of the research show that; 1. Increase contribution to reform, and increase trust between the government and society; 2. Improving Services: Ensuring the availability of basic infrastructure such as roads, electricity, clean water; 3. Helping to Achieve a Policy, actively involving village communities in the planning process; 4. Help contribute to policies, individuals, groups or organizations; 5. Increase contribution to reform, increase contribution to reform in village offices; 6. Increase trust between the government and the community. Sustainable and comprehensive efforts are needed to increase trust between the village government and the community.